Research on the characteristics of spatial and temporal differentiation and driving factors of green development — from the perspective of the counties in China - Tong, Xin; Wang, Ran (Frontiers in Environmental Science, 2026)
As an important level in the administrative system, counties have abundant natural and agricultural resources and play a key role in promoting green development strategies. This article uses the entropy method to construct a comprehensive evaluation index system for green and low-carbon development from five dimensions: green innovation, green coordination, green efficiency, green openness, and green sharing. It uses econometric methods such as Moran’s index and kernel density estimation to empirically analyze the level of green and low-carbon development in Chinese counties, differentiation characteristics, and spatial effects. Furthermore, geographically weighted regression model is introduced to explore and analyze the driving factors of various variables on the differences of green development in Chinese counties. The study finds the following: From a temporal perspective, the overall level of green development in Chinese counties shows a fluctuating upward trend; From the perspective of spatial evolution, the green development of Chinese counties presents a regional distribution characteristic of “moderate distribution in west, high in the east and low in west”; The level of green development in counties has a significant spatial positive correlation. The driving factors of economic development level, green technology innovation, and government support mainly have a positive impact on the green development of Chinese counties, while the quality of human resources mainly has a negative impact. The research results emphasize that there is obvious spatial heterogeneity in the impact of each driving factor. By implementing differentiated green development strategies to alleviate resource and environmental problems between counties, deepening the concept of green and low-carbon development, optimizing the industrial layout structure of counties, and adhering to the strategy of innovation driven development, suggestions can help counties achieve sustainable development goals.